(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Tcherevko S. V. Assessing the Needs of the Target Group for Their Health-consciousnes. The article describes the method of assessing the needs of the target group for their health-consciousness, phases of evaluation and results. It is proved the feasibility of using this method with students as a target group. The attention is paid on the fact that the proposed method of assessing the needs of their target group for health-consciousness is retrospective and predictive in nature and can be used mainly for the analysis of situations based on their positive or negative impact on the lives of the target group and each of its members. Method of assessing the needs of the target group for health-consciousness makes it possible to delineate as a common problem, and some of its components.